2011
DOI: 10.1371/journal.pone.0024484
|View full text |Cite
|
Sign up to set email alerts
|

Delta1 Expression, Cell Cycle Exit, and Commitment to a Specific Secretory Fate Coincide within a Few Hours in the Mouse Intestinal Stem Cell System

Abstract: The stem cells of the small intestine are multipotent: they give rise, via transit-amplifying cell divisions, to large numbers of columnar absorptive cells mixed with much smaller numbers of three different classes of secretory cells - mucus-secreting goblet cells, hormone-secreting enteroendocrine cells, and bactericide-secreting Paneth cells. Notch signaling is known to control commitment to a secretory fate, but why are the secretory cells such a small fraction of the population, and how does the diversity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
86
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(95 citation statements)
references
References 55 publications
(83 reference statements)
7
86
2
Order By: Relevance
“…Notch plays an essential role in crypt cell proliferation 5,29 but it is only recently that lineage tracing and Notch inhibition studies have demonstrated that active Notch signaling is present 24,33 and required for maintenance of ISCs 7,34 . Notch inhibition led to reduced proliferation, loss of the stem cell marker, Olfm4, and apoptosis of CBCs, indicating that active Notch signaling is required for survival of Lgr5 + CBCs.…”
Section: Discussionmentioning
confidence: 99%
“…Notch plays an essential role in crypt cell proliferation 5,29 but it is only recently that lineage tracing and Notch inhibition studies have demonstrated that active Notch signaling is present 24,33 and required for maintenance of ISCs 7,34 . Notch inhibition led to reduced proliferation, loss of the stem cell marker, Olfm4, and apoptosis of CBCs, indicating that active Notch signaling is required for survival of Lgr5 + CBCs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as it was demonstrated that the POU3F3 gene could interact with DLL1 and Sox2 promoters, activating their transcription (Catena et al, 2004;Castro et al, 2006), POU3F3 is involved into regulating cell proliferation via cell-cycle (G1) arrest and apoptosis through its influence on DLL1 and Sox2 (Otsubo et al, 2008;Stamataki et al, 2011). Meanwhile, since DLL1 acts as a Notch ligand, the influence of DLL1 expression by linc-POU3F3 also affect the Notch signaling, which regulates multiple cellular processes, including differentiation, proliferation, and cell fate decisions, and required for organogenesis and tissue homeostasis (Artavanis-Tsakonas et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Within crypts, the Notch ligand Dll1 is expressed by secretory cell progenitors at cell positions just above the stem cell zone, which are immediate descendants of Lgr5+ cells [32,33]. Lineage tracing using a Dll1-GFP-IRESCreERT2 allele has shown that, during homeostasis, these cells generate small, short lived clones that comprise goblet cells, Paneth cells, tuft cells, and enteroendocrine cells.…”
Section: Dedifferentiation Of Committed Progenitor Cells In the Intesmentioning
confidence: 99%